A Model of Chronic Exposure to Unpredictable Mild Socio-Environmental Stressors Replicates Some Spaceflight-Induced Immunological Changes - Gaignier, Fanny; Legrand-Frossi, Christine; Stragier, Emilien; Mathiot, Julianne; Merlin, Jean-Louis; Cohen-Salmon, Charles; Lanfumey, Laurence; Frippiat, Jean-Pol (Frontiers in Physiology, 2018)
During spaceflight, astronauts face radiations, mechanical, and socio-environmental stressors. To determine the impact of chronic socio-environmental stressors on immunity, we exposed adult male mice to chronic unpredictable mild psychosocial and environmental stressors (CUMS model) for 3 weeks. This duration was chosen to simulate a long flight at the human scale. Our data show that this combination of stressors induces an increase of serum IgA, a reduction of normalized splenic mass and tends to reduce the production of pro-inflammatory cytokines, as previously reported during or after space missions. However, CUMS did not modify major splenic lymphocyte sub-populations and the proliferative responses of splenocytes suggesting that these changes could be due to other factors such as gravity changes. Thus, CUMS, which is an easy to implement model, could contribute to deepen our understanding of some spaceflight-associated immune alterations and could be useful to test countermeasures.